Correlation between inflammatory markers and organ dysfunction among Intensive Unit Care patients - Mousavi Jazayeri, Seyed Mohammad Hosein; Safaiyan, Abdolrasoul; Ostadrahimi, Alireza; Hashemzadeh, Shahryar; Salehpour, Firouz (Progress in Nutrition, 2018)
Background: Nutrition in the Intensive Care Unit (ICU) encounters a variety of challenges. This study aimed to examine the correlation of Tumor Necrosis Factor-alpha (TNF-α) and high sensitive C-reactive protein (hs-CRP) with the Sequential Organ Failure Assessment (SOFA) score in traumatic ICU patients. Patients and Methods: Twenty five critically ill patients were recruited for assessment of the inflammatory factors’ correlation with the SOFA score. Statistical analyses were done using parametric tests. Results: Statistical analysis showed a strong correlation between TNF-α on day 3 of admission with SOFA scores on days 5 and 7 (r> 0.5). A similarly strong correlation also was seen between hs-CRP and SOFA on days 3 and 5 (r>0.5). Conclusion: The study results showed serum levels of TNF-α on day 3 of admission can predict organ dysfunction in traumatic ICU patients and TNF-α is a better prognostic factor than hs-CRP.